Development of Memristor Based Circuits. - Iu, Herbert Ho-Ching (World Scientific series on nonlinear science. Monographs and treatises., 2012)
In 1971, Leon O. Chua presented the formulation of a memristor, which was postulated as the fourth circuit element in electrical circuit theory - one that could join the existing core group of elements: capacitor, resistor and inductor. For over thirty years, the memristor had held no significance in circuit theory. Then in 2008, a group of scientists from Hewlett-Packard Labs (HP) developed a working memristor. Although the solid state implementation of the memristor inspired appreciable interest in developing applications, memristors are not yet available on the market to date. HP labs do no.